2008
DOI: 10.1007/s10552-007-9104-7
|View full text |Cite
|
Sign up to set email alerts
|

The changing patterns of bladder cancer in Egypt over the past 26 years

Abstract: Objective-To evaluate temporal changes in histopathological types of bladder cancer and to assess associated changes in demographic, epidemiologic, and lifestyle risk factors.Methods-We abstracted data from all available medical records from the National Cancer Institute of Cairo University (NCI-Cairo). Six calendar years representing 5-year periods between 1980 and 2005 were evaluated. Information on demographics, schistosomal infection, clinical symptoms of bladder cancer, and tumor pathology was abstracted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 27 publications
7
114
1
2
Order By: Relevance
“…A S. haematobium-associated bladder cancer incidence of 3-4 cases per 100,000 has been estimated (Shiff et al, 2006). Felix et al (2008) showed that the occurrence of transitional cell carcinoma (TCC) of the bladder has supplanted SCC in Egypt following a major decline in the prevalence of urinary schistosomiasis. Such a decline in the pattern of this infection suggests the importance of schistosome-associated bladder cancer that, elsewhere, may be more widespread than is presently thought (Shiff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A S. haematobium-associated bladder cancer incidence of 3-4 cases per 100,000 has been estimated (Shiff et al, 2006). Felix et al (2008) showed that the occurrence of transitional cell carcinoma (TCC) of the bladder has supplanted SCC in Egypt following a major decline in the prevalence of urinary schistosomiasis. Such a decline in the pattern of this infection suggests the importance of schistosome-associated bladder cancer that, elsewhere, may be more widespread than is presently thought (Shiff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, they show more than seven layer thick urothelium with cells without any cytological atypia. (13,16,17) On the contrary, low-grade papillary urothelial carcinoma will show thickened urothelium with papillary fronds with minimum cytological atypia. (3,4,6,18) Very rarely these lowgrade tumour would also recur if there was an evidence of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A fall in the prevalence rate of schistosomiasis from 1980 to 2005 due to a public health intervention was followed by a six-fold lower rate of SCC, clearly suggesting a cause and effect relationship [24].…”
Section: Clinical Manifestationsmentioning
confidence: 99%